Archived Cytogenetic Cell Pellets Used to Detect a BCR::ABL1 Driver Mutation Eight Years before Disease Presentation - Ramakrishnan Sasi; Michelle Spruill; Peter L. Perrotta (Case Reports in Hematology)
Evidence suggests that the earliest genetic events in the evolution of a cancer can predate diagnosis by several years or decades. In chronic myeloid leukemia (CML), the BCR::ABL1 fusion driver mutation can be present for an extended period before clinical disease manifests. The time between the BCR::ABL1 occurrence and symptom onset is referred to as the latency period. Though modeling studies predict this latency period is no more than ten years, it is still unclear how long it can be. We present a case of a patient referred for suspected CML. Both karyotype and FISH analysis identified the t(9;22)(q34;q11.2) translocation resulting in the Philadelphia chromosome formation in 98.5% of cells analyzed. The patient responded to imatinib and achieved a sustained complete hematologic and cytogenetic remission. Clinical history revealed that the same patient presented eight years previously with anemia. Various non-neoplastic conditions were excluded, and a bone marrow biopsy was performed to rule out MDS. Cytogenetic analysis at that time revealed del(20q) as the sole abnormality in all 20 cells analyzed. No treatment was given since the presence of isolated del(20q) is not considered evidence of MDS in the absence of diagnostic morphologic criteria. Retrospective FISH analysis of archived bone marrow pellets from this previous specimen revealed the presence of BCR::ABL1 in 1.8% of cells. A clonal population of cells harboring the BCR::ABL1 fusion was unambiguously detected in this patient’s archived bone marrow pellet obtained eight years before the current CML diagnosis. This case demonstrates that Carnoy’s fixed nuclear pellets stored in cytogenetic laboratories are suitable for detecting driver mutations years before disease presentation. Such archived material may be useful for the retrospective studies needed to better understand the initiation and subsequent development of hematological malignancies. By identifying individuals who are at increased risk, it may be possible to initiate preventive measures or begin treatment at an earlier stage before disease progression.